Education Sector Development Plan 2002 to 2007: Volume 1 - Policy, Strategy and Logical Framework - St. Vincent and the Grenadines. Ministry of Education, Youth and Sports (Ministry of Education, Youth and Sports, 2002)
The Education Sector Development Plan (ESDP) presents a set of policy directions, targets, and strategies to sustain educational development in St. Vincent and the Grenadines until 2007. The primary purpose, as articulated in the document is to provide strategies and a timeframe for delivering education of a quality that raises levels of achievement of all learners, enabling them to benefit as individuals and to contribute to national and regional development. The ESDP concentrate on 10 sub-sectors, each with its own goals and policy objectives. 1) Management, administration, and governance; 2) Early childhood education; 3) Primary and all-age school education; 4) Secondary education; 5) Tertiary and higher education; 6) Special education 7) Adult and continuing education; 8) The teaching profession; 9) Technical and vocational education and training; and 10) Libraries, documentation, and archives. Volume 1 provides the policy, strategy, and logical framework, and Volume 2 presents the action plan.
Keywords: Development plans